Adaptive Assembly: Maximizing the Potential of a Given Functional Peptide with a Tailor-Made Protein Scaffold. Issue 9 (17th September 2015) - Watanabe, Hideki; Honda, Shinya
Summary: Protein engineering that exploits known functional peptides holds great promise for generating novel functional proteins. Here we propose a combinatorial approach, termed adaptive assembly, which provides a tailor-made protein scaffold for a given functional peptide. A combinatorial library was designed to create a tailor-made scaffold, which was generated from β hairpins derived from a 10-residue minimal protein "chignolin" and randomized amino acid sequences. We applied adaptive assembly to a peptide with low affinity for the Fc region of human immunoglobulin G, generating a 54-residue protein AF.p17 with a 40, 600-fold enhanced affinity. The crystal structure of AF.p17 complexed with the Fc region revealed that the scaffold fixed the active conformation with a unique structure composed of a short α helix, β hairpins, and a loop-like structure. Adaptive assembly can take full advantage of known peptides as assets for generating novel functional proteins. Graphical Abstract: Highlights: A segment-based combinatorial approach termed adaptive assembly was developed Adaptive assembly generated a tailor-made protein scaffold for a functional peptide The developed protein scaffold achieved 40, 600-fold functional enhancement Adaptive assembly takes advantage of peptides as assets to create novel proteins Abstract : Watanabe et al. propose a segment-based combinatorial approach termed adaptive assembly that generates a tailor-made protein scaffold for a given functional peptide. Adaptive assembly can achieve significant functional enhancement without relying on known protein structures.